2016
DOI: 10.21697/fp.2015.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Metodyka edukacji osób w starszym wieku. Podstawowe wskazówki i zasady

Abstract: W artykule podjęto temat metodyki nauczania osób w starszym wieku w zakresie: planowania zajęć, określania ich celów, metod, treści, przyswajania wiedzy oraz oceny postępów uczenia się. Szczególną uwagę poświęcono sformułowanym zasadom nauczania seniorów.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…As stated in section 2.2 of the paper, we provide a teaching perspective based on the research carried out among Polish teachers of seniors. According to Kilian (2015), "the role of teachers and educations is maximizing the benefits of learning in late adulthood by adjusting the methods of teaching to recognized and real needs and abilities of seniors" (p. 182; authors' translation). The outputs of the conducted research have shown that the vast majority of teachers are aware of the aforementioned attitude -94% of our respondents admitted to adjusting methods and techniques when teaching foreign languages to older learners.…”
Section: Authors' Research Results and Discussionmentioning
confidence: 99%
“…As stated in section 2.2 of the paper, we provide a teaching perspective based on the research carried out among Polish teachers of seniors. According to Kilian (2015), "the role of teachers and educations is maximizing the benefits of learning in late adulthood by adjusting the methods of teaching to recognized and real needs and abilities of seniors" (p. 182; authors' translation). The outputs of the conducted research have shown that the vast majority of teachers are aware of the aforementioned attitude -94% of our respondents admitted to adjusting methods and techniques when teaching foreign languages to older learners.…”
Section: Authors' Research Results and Discussionmentioning
confidence: 99%
“…Osoby biorące udział w badaniu zdawały sobie sprawę z faktu, że w starości często przerzedzają się sieci społecznych kontaktów. Zaprzestanie pełnienia dotychczasowych ról i zmniejszenie społecznych aktywności w świecie zewnętrznym powoduje zmiany w obszarze kompetencji społecznych (Kilian, 2020). Redukcja kontaktów społecznych wśród osób starszych związana jest z teorią wycofania, wedle której osoby starsze wycofują się z dotychczasowych relacji i ról społecznych, w celu przygotowania się na odejście i ustąpienia miejsca młodszym pokoleniom (Szukalski, 2005).…”
Section: Znaczenie Nadawane Przez Seniorów Aktywności Twórczej W Aspe...unclassified
“…According to Kilian (2015), planning classes for the elderly can be divided into two stages. The first stage is planning done by the teacher, and the second one requires participants' engagement in making decisions as to their own education that renders them partially responsible for their learning effects.…”
Section: Planning Classes/contentmentioning
confidence: 99%
“…Systematic and comprehensive assessment contributes to strengthening their educational motivation and, in consequence, boosting their self-confidence. Kilian (2015) states that formal progress assessment that consists in getting grades or awarding certificates does not come into play when teaching mature age. Such practices may only discourage course participants from attending classes.…”
Section: Planning Classes/contentmentioning
confidence: 99%